2012
DOI: 10.5424/fs/2012213-02104
|View full text |Cite
|
Sign up to set email alerts
|

Cork oak (Quercus suber L.) wood hygroscopic properties and dimensional stability

Abstract: Cork oak (Quercus suber L.) wood has a potential for high value uses because of its strength and aesthetic properties but one obstacle is the lack of knowledge of the wood-water relations. Variations in wood equilibrium moisture content, density and dimensions were studied at air temperatures of 22°C and 27°C (representing acclimatized homes and summer non-acclimatized homes, respectively) varying from 80% to 30% of relative humidity.For indoor uses (22-27°C, 50-65% of relative humidity), the wood equilibrium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Zhang et al, 1993;Guilley et al, 1999Guilley et al, , 2004Bergès et al, 2008), but other oaks have also attracted attention, namely species growing in more southern regions (e.g. Knapič et al, 2008;Leal et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al, 1993;Guilley et al, 1999Guilley et al, , 2004Bergès et al, 2008), but other oaks have also attracted attention, namely species growing in more southern regions (e.g. Knapič et al, 2008;Leal et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the densities analyzed, it was observed that they decrease when the height in the stem increases (Table 5). Knapic et al (2011) and Leal et al (2012) found similar behavior in Quercus faginea and Q. suber L., respectively. The anhydrous density of sapwood wood according to the mean is like the reports for Q. sartorii and Q. mexicana wood .…”
Section: Densitymentioning
confidence: 62%
“…This causes a reduction in the permeability of the wood, so the moisture content is low. The behavior presented in the wood of Quercus suber L. is the opposite to this convention (Leal et al 2012).…”
Section: Moisture Contentmentioning
confidence: 88%
See 1 more Smart Citation
“…Which differ in values reported for Q. convallata Trel. (22), Q. suber L. (28), and Q. macdougallii Martínez (39). Moreover, it was noted that Q. aegilops has a very high proportion of the cell wall (55.24%).…”
Section: Physical Propertiesmentioning
confidence: 99%